Shaping Gender Policy in Turkey Grassroots Women Activists, the European Union, and the Turkish State - Marshall, Gül Aldıkaçtı (SUNY Press Open Access, 2013)
Timely analysis of the ways in which women grassroots activists, the European Union, and the Turkish state are involved in shaping gender policies in Turkey.Shaping Gender Policy in Turkey uncovers how, why, and to what extent Turkish women, in addition to the Turkish state and the European Union, have been involved in gender policy changes in Turkey. Through analysis of the role of multiple actors at the subnational, national, and supranational levels, Gül Aldıkaçtı Marshall provides a detailed account of policy diffusion and feminist involvement in policymaking. Contextualizing the meaning of gender equality and multiple approaches to women's rights, she highlights a pivotal but neglected dimension of scholarship on Turkey's candidacy for European Union membership. This book represents one of the few works providing a multilevel analysis of gender policy in predominantly Muslim countries, and highlights Turkey's role at a time of swift structural changes to several political regimes in the Middle East.Gül Aldıkaçtı Marshall is Associate Professor of Sociology at the University of Louisville.